The Problem of Proving the Paternity of Children Born of ISIS Members and Yazidis - Sarbast Hussein Abdullah.; Kamal Muhamad Abubakr (QALAAI ZANIST JOURNAL, 2023)
ISIS has committed many crimes that are considered crimes against humanity, the most famous of which is the crime of rape, forced marriage and enslavement of Yazidi women in Iraq, which ISIS calls (slaves). This resulted in the birth of children born to ISIS fathers and surviving Yazidi mothers who suffer a lot of suffering and problems about their rights and fate. The opinions of jurists and legal scholars differed about the proportions of these children, and it is more likely that the children born as a result of rape or enslavement of women are attributed to their mothers because they were born illegally, so their mothers become like the father to them in terms of rights and obligations, registration in official departments, issuance of civil status identity and national card, and obtaining citizenship Iraqi, and others, and based on the Iraqi Nationality Law, Paragraph (A) of Article (3), Iraqi nationality can be obtained for the children of Yazidi survivors from their mothers.